Seeking shelter : a working mother, her children, and a story of homelessness in America - Hobbs, Jeff, 1980- (Scribner, 2025)
"In the tradition of Evicted and Invisible Child, Jeff Hobbs masterfully explores America's housing crisis through the real-life story of Evelyn. This is Hobbs's first book since The Short and Tragic Life of Robert Peace that focuses on a single character and her extraordinarily illuminating journey. In 2018, poverty and domestic violence cast Evelyn and her children into the urban wilderness of Los Angeles, where she avoids the family crisis network that offers no clear pathway for her children to remain together and in a decent school. For the next five years, Evelyn works full time as a waitress yetremains unable to afford legitimate housing or qualify for government aid. All the while she strives to provide stability, education, loving memories, and college aspirations for her children even as they sleep in motels and in her car, living in fear of both her ex and the nation's largest child welfare agency. Eventually Evelyn encounters Wendi Gaines, a recently trained social worker who decades earlier survived her own abusive marriage and housing crisis. Evelyn becomes one of Wendi's first clients, and the relationship transforms them both. Told from the perspectives of Evelyn, Wendi, and Evelyn's teenaged son, Orlando, Seeking Shelter is a powerful and urgent exploration of the issues of homelessness, poverty, and education in America-a must-read for anyone interested in understanding not just social inequality and economic disparity in our society but also the power of a mother's love and vision for her kids."--